(untitled) (Nepal Medical College Journal, 2022)
Palmaris longus is a thin fusiform shaped muscle which terminates as a long slender tendon and enters the palmar aponeurosis of the hand. It is also one of the most variable muscles in the body. The main objective of this study was to detect its tendon in both hands and to compare and analyse it in relation to gender and hand dominance. An observational, descriptive study was conducted over a period of 11 months from October 2021 – August 2022 in the Department of Human Anatomy of Nepal Medical College and Teaching hospital, Gokarneshwor – 8, Kathmandu, Nepal. Following tests were conducted for its detection. 1. Schaeffer’s, 2. Thompson’s, 3. Mishra’s test I, 4. Mishra’s test II and Pushpakumar’s test. The results obtained showed that presence of left palmaris longus was more in left handed individuals which was statistically significant with p – value of 0.025. Similarly, presence of right palmaris longus was more in right hand dominant participants. Among the left hand dominant participants, left palmaris longus agenesis was more common in female which was also found to be statistically significant with p-value of 0.009. The knowledge regarding the palmaris longus tendon is of growing interest to surgeons these days for its augmentation, ptosis correction and in facial paralysis management. It gains its importance for autograft as it fulfills the requirement of length, diameter and availability. Hence the study regarding the palmaris longus tendon in relation to its hand dominance and gender can be helpful to surgeons working in various fields.